Cytokine imbalance in patients with systemic sclerosis and resilience: the key role of interleukin-6 (2019)
OBJECTIVES: Resilience, the ability to respond positively to adverse events, may be influenced by long-term stressors and autoimmune/inflammatory conditions such as systemic sclerosis (SSc). Since the immune system plays a role in the development of resilience, we aimed to evaluate the relationship between a panel of cytokines and resilience in patients with SSc. METHODS: Thirty-five consecutive women with established SSc were involved in this exploratory study. Clinical characteristics, including severity of symptoms and resilience, a panel of 15 serum cytokines and 17 autoantibodies were assessed simultaneously. Multivariate methods were used to analyse the data. RESULTS: Interleukin-6 (IL-6) levels were associated with severity of symptoms (?=1.8395, p=0.04), and low resilience scores (?= -0.581120, p=0.02). Furthermore, resilience was not associated with clinical manifestations nor polyautoimmunity. Cytokine levels did not significantly differ between groups based on regular physical activity. CONCLUSIONS: The results highlight the importance of IL-6 as a key mediator in the altered cytokine network of SSc.